Aung San Suu Kyi's Verdict: Implications for ASEAN - Caballero-Anthony, Mely (2016)
The guilty verdict by a Myanmar court on Aung San Suu Kyi for breaking the terms of her house arrest is a serious blow to the standing of ASEAN both locally and internationally. It comes less than a month after ASEAN members, including Myanmar, accepted the Terms of Reference of their agreement on human rights at a meeting in Thailand.